Предмет: Математика,
автор: Аноним
162. Упростите выражения: a) 2 + (b-4); 6) −(3 − y) + 7; д) 2(x + y) – 2x; в) (3 +y) - 42; г) (x-5) + (x+7); e) 4(a-2b) + 8b.
Ответы
Автор ответа:
2
Ответ:
Пошаговое объяснение:
a) 2 + (b-4)= 2+ в - 4= в -2;
6) −(3 − y) + 7= -3 +у + 7= у+7 - 3 = у+4
д) 2(x + y) – 2x=2х+ 2у - 2х= 2у;
в) (3 +y) - 42=3 + у - 42 = у - 39
г) (x-5) + (x+7)= х - 5 + х +7 =2х +2;
e) 4(a-2b) + 8b= 4а -8b+8b= 4а
Автор ответа:
1
Пошаговое объяснение:
1) 2 + (в - 4) = 2 + в - 4 = -2 + в
2) -(3 - у) + 7 = -3 + у + 7 = 4 + у
3) 2(х + у) - 2х = 2х + 2у - 2х = 2у
4) (3 + у) - 42 = 3 + у - 42 = -39 + у
5) (х - 5) + (х + 7) = х - 5 + х + 7 = 2х + 2
6) 4(а - 2в) + 8в = 4а - 8в + 8в = 4а
Похожие вопросы
Предмет: Математика,
автор: andreygrachev863
Предмет: Математика,
автор: alenakosinova0190
Предмет: Алгебра,
автор: blmejmblmejmn
Предмет: Физика,
автор: gno10121998